Kualitas Pelayanan Pembuatan Akta Lahir di Dinas Kependudukan dan Catatan Sipil Kota Batam - Sahar Bin Bahari; Karol Teovani Lodan (Universitas Batanghari Jambi, 2023)
The purpose of this study is to describe and analyze the quality of service for making birth certificates at the Batam City Population and Civil Registry Office. This research is a qualitative research with a descriptive approach. The reliability indicator, the birth certificate service at the Batam City Population and Civil Registry Office has been provided in accordance with all the information obtained by the community at the beginning. Tangibles indicators, some infrastructure facilities at the Batam City Population and Civil Registration Office are still not sufficient. Responsiveness indicator, Batam City Population and Civil Registry Office has had a good speed in providing birth certificate making services. Assurance indicator, Batam City Population and Civil Registry Office already has employees with good behavior in providing birth certificate making services. As an indicator of empathy, the Batam City Population and Civil Registry Office has tried to find out what the aspirations and expectations of the community are regarding services for making birth certificates.